An overview of the Brazilian contributions to Green Analytical Chemistry - GAMA, MARIANA R.; MELCHERT, WANESSA R.; PAIXÃO, THIAGO R.L.C.; ROCHA, FÁBIO R.P. (Anais da Academia Brasileira de Ciências, 2019)
Green Analytical Chemistry (GAC) is a research field that seeks for more sustainable analytical approaches to minimize the toxicity and amounts of wastes without hindering the analytical performance. This is a trend in Analytical Chemistry worldwide and because of the diversity of innovations on this subject, Brazil stands out as the third in the list of the main contributors to GAC, with ca. 11.2% of the published articles. Significant innovations and interesting applications in several fields have been presented and Brazil is continuously moving from Chemistry to Green Chemistry also in the Analytical Chemistry field. Selected contributions for sample preparation, spectro- and electroanalysis, separation techniques, chemometrics, and also procedures for point-of-care measurements are critically reviewed.